RESPON PETANI PADI PASANG SURUT TERHADAP PROGRAM SEKOLAH LAPANGAN PENGENDALIAN HAMA TERPADU (SLPHT) (Kajian Survey Di Desa Pulau Borang Kecamatan Banyuasin I Kabupaten Banyuasin) - Silviana, Novia; Afriyatna, Sisvaberti (Societa: Jurnal Ilmu-Ilmu Agribisnis, 2015)
This study aime to measure the farmer’s respon of SLPHT of Pulau Borang village Banyuasin I District Banyuasin regency.The reseacrh was implemented in the of Pulau Borang village Banyuasin I District Banyuasin regency. Location determination is done intentionally (purposive sampling). The method used in this study is a survey method. Sampling using a surfeited sampling method in which the entire population saturated serve as the research sample.Total population of farmers participating in the SLPHT is 25 people. Data collection in done by taking two kinds of data primary and secondary data. To answer the first goal, tabulate all data and continued with quantitative explanation. The result shows that the response of farmers in the SLPHT activities included in the high criteria with a mean score of 55,60. This shows that farmers carry out their farming activities in accordance with the advice and information provided by PPL in the activities of SLPHT.